PENDRIN REDUCTION IS ASSOCIATED WITH ACUTE INTRAVENOUS SODIUM CHLORIDE LOADING IN PATIENTS WITH PRIMARY ALDOSTERONISM. (April 2021) - Wu, Aihua; Wolley, Martin J.; Wu, Qi; Cowley, Diane; Gordon, Richard D.; Fenton, Robert A.; Stowasser, Michael
Abstract : Objective: Primary aldosteronism (PA) is a common, potentially curable form of hypertension characterised by excessive, autonomous aldosterone production. In the distal renal tubule, aldosterone is involved in volume homeostasis by modulation of NaCl reabsorption via the epithelial Na+ channel (ENaC), the NaCl cotransporter (NCC) and the Cl-/HCO3- exchanger (pendrin). Na+ loading suppresses plasma aldosterone but its effects on these proteins in humans remain unclear. Design and method: Urine samples were collected before and 1 h after a 4 h 2L 0.9% saline infusion from 13 (F9/M5) subjects including 10 confirmed with PA and 3 in which PA was excluded [herein designated low renin hypertension (LRH)]. Urinary exosomes were harvested by ultracentrifugation and analysed by LC-MS/MS. Results: Plasma aldosterone decreased (P < 0.05) from 623 [312, 2210] (median [range]) to 338 [197, 2330] pmol/L in confirmed PA and from 223 [180, 256] to 117 [110, 133] pmol/L in LRH. There were no changes in plasma K+ (pre 3.4 [2.6, 4.3] vs post 3.6 [2.6, 3.9] mmol/L in PA; pre 4.1 [3.6, 4.1] vs post 4.0 [3.9, 4.0] mmol/L in LRH). LC-MS/MS demonstrated decreases in abundance of pendrin (21.5%, P < 0.01) and aquaporin-2 (AQP2) (42.9%, P < 0.01) in urinary exosomes and a trend towards a decrease in NCC (20%, P = 0.07) in patients with PA. No changes were seen in those with LRH. PA patients had higher baseline pendrin abundance (1.2 [1.0, 2.1]) than LRH patients (0.7 [0.5, 1.0]) (P < 0.05), but there was no difference in baseline AQP2. In all 13 subjects combined, baseline pendrin correlated positively with plasma aldosterone (P = 0.02, r2 = 0.32) and negatively with plasma K+ (P = 0.02, r2 = 0.35), whilst no correlations were observed between AQP2 and aldosterone or K+. Delta Pendrin (P = 0.04, r2 = 0.3) and delta AQP2 (P = 0.01, r2 = 0.58) positively correlated with delta plasma aldosterone. Conclusions: In PA, reduction in pendrin during saline infusion may be due to falling plasma aldosterone in response to NaCl loading. Although also correlating with reduction in aldosterone, a more likely explanation for the reduction in AQP2 may be a fall in plasma vasopressin induced by water loading. Different observations in LRH require validation with larger numbers.